Nanotextured gold coatings on carbon nanofiber scaffolds as ultrahigh surface-area electrodes - COLAVITA, PAULA (My University, 2012)
High surface area metal electrodes are desirable for applications in energy storage and energy conversion. Here, the formation and electrochemical characterization of a hybrid material made by electroless deposition of gold onto a scaffolding of vertically aligned carbon nanofibers is described. Vertically aligned carbon nanofibers, ~80 nm in diameter, provided mechanical support and electrical contact to the highly textured nanoscale gold coatings. By chemically functionalizing the nanofiber surfaces and then using electroless deposition methods, a highly textured metal coating was formed. The electrochemical response of these ?nano-on-nano? hybrid electrodes was characterized using electrochemical methods. The results show that using the metallic coatings can increase the electrochemically active surface area by up to a factor of 10 compared with the starting carbon nanofiber scaffolds. The electrochemical response of the electrodes was modulated by varying the deposition time of the gold.
PUBLISHED
Keywords: Physical chemistry; Gold